2018
DOI: 10.1002/ajmg.a.38853
|View full text |Cite
|
Sign up to set email alerts
|

Growth in achondroplasia: Development of height, weight, head circumference, and body mass index in a European cohort

Abstract: As growth references for achondroplasia are limited to reports from United States, Japan, Argentina, and Australia, the aim of this study was to construct growth references for height, weight, head circumference, and body mass index (BMI) from a European cohort of children with achondroplasia and to discuss the development of these anthropometric variables. A mix of cross-sectional and longitudinal, retrospective, and prospective data from 466 children with achondroplasia and 4,375 measuring occasions were mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 42 publications
3
69
1
7
Order By: Relevance
“…Obesity and high BMI are frequently reported in achondroplasia . However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, and even more in individuals of disproportionate short stature, such as achondroplasia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and high BMI are frequently reported in achondroplasia . However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, and even more in individuals of disproportionate short stature, such as achondroplasia .…”
Section: Discussionmentioning
confidence: 99%
“…18,22,32,[60][61][62][63] However, BMI and other anthropometric measurements are poor predictors of body fat and fat distribution, 64 and even more in individuals of disproportionate short stature, such as achondroplasia. 32,60,65 In a recently published paper, the authors found an atypical obesity with preferential abdominal obesity in achondroplasia children. 66 The obesity was not associated with classical complications, such as diabetes or hypercholesterolemia, suggesting an uncommon energy metabolism in achondroplasia.…”
Section: Medical Complications Health Characteristics and Psychosomentioning
confidence: 99%
“…Grossly deviant body proportions due to short limbs are typical for achondroplasia (Horton, Rotter, Rimoin, Scott, & Hall, ; Murdoch et al, ; Nehme, Riseborough, & Tredwell, ; Wynne‐Davies, Walsh, & Gormley, ). The constitutionally activating fibroblast growth factor receptor 3 (FGFR3) mutation (Rousseau et al, ; Shiang et al, ) confers major growth inhibition of the extremities causing disproportional, extreme short stature with an adult height of about 133/124 cm in men/women (Merker et al, ). A major bodily disproportion is thus a signature for achondroplasia, yet documentation of body proportion development is limited to graphical illustrations of sitting height (Nehme et al, ), upper and lower body segment (Horton et al, ), and upper‐to‐lower body segment ratio (Hoover‐Fong, Schulze, McGready, Barnes, & Scott, ) and tabled reference values are not available.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with growth velocities of non-ACH children from the United States, in a sample processed with the same mathematical method, the growth velocity of ACH-children was lesser in magnitude (Berkey & Reed, 1987). This growth retardation during infancy, determine the severe growth deficit at 2 years of age for ACH children described in different populations (del Pino et al, 2010;Hoover-Fong et al, 2017;Merker et al, 2018;Tofts et al, 2017).…”
Section: Children's Patterns Of Growthmentioning
confidence: 99%
“…During infancy and childhood height falls progressively and in adolescents, is approximately 5.00 SDS below the 50th centile for Argentine and others non-ACH populations with a mean adult height of −6.42 and −6.72 SDS, for males and females, respectively (del Pino et al, 2010;Hoover-Fong, McGready, Schulze, Alade, & Scott, 2017;Lejarraga, del Pino, Fano, Caino, & Cole, 2009;Merker et al, 2018;Tofts, Das, Collins, & Burton, 2017).…”
Section: Introductionmentioning
confidence: 98%